Soft shapes : Animals. - Ski, Jenn (Norwalk : Innovativekids, 2010)
On the Farm, the animals all have something to say. To learn the sounds they make, pull out the pieces and play.Made entirely of child-safe foam with pop-out play pieces, these huggable, squeezable, touchable favorites are all dressed up with color illustrations. It's the same great foam-filled fun but now with a fresh new face! What sounds do the animals make? Pop out the foam pieces to reveal the answers.
Soft shapes.
Preschool.
Keywords: Animal sounds; Farm animals; Sounds of animals